2022
DOI: 10.3389/fnana.2022.844737
|View full text |Cite
|
Sign up to set email alerts
|

Reelin Alterations, Behavioral Phenotypes, and Brain Anomalies in Schizophrenia: A Systematic Review of Insights From Rodent Models

Abstract: Reelin is an extracellular matrix glycoprotein reduced in brain regions (the prefrontal cortex and the hippocampus) of patients with schizophrenia. There are diverse rodent models of schizophrenia that mimic patient symptoms based on various causal theories; however, likely shared reelin alterations have not yet been systematically assessed in those models. A systematic review of the literature was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) model. Articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Similar to the Dab1 gene, the Reelin gene is also known to exhibit haploinsufficiency (Liu et al, 2001;Carboni et al, 2004;Qiu et al, 2006;Nullmeier et al, 2011;Bouamrane et al, 2016;Wang et al, 2019), and reduced Reelin levels have been observed in the brains of patients with schizophrenia (Impagnatiello et al, 1998;Guidotti et al, 2000), bipolar disorder (Guidotti et al, 2000), autism (Fatemi et al, 2001;Fatemi et al, 2005), and Alzheimer's disease (Chin et al, 2007). Moreover, heterozygous reeler mice and Reelin ΔC-KI mice exhibit similar neurochemical, behavioral, and cognitive abnormalities to those observed in autism or schizophrenia (Costa et al, 2001;Tremolizzo et al, 2002;Carboni et al, 2004;Nullmeier et al, 2011;Sakai et al, 2016;Sanchez-Hidalgo et al, 2022). The anatomical abnormalities we observed in heterozygous yotari mice may also be related to behavioral defects because layer 1 and hippocampus are essential for higher-order cognitive functions (Hainmueller and Bartos, 2020;Schuman et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the Dab1 gene, the Reelin gene is also known to exhibit haploinsufficiency (Liu et al, 2001;Carboni et al, 2004;Qiu et al, 2006;Nullmeier et al, 2011;Bouamrane et al, 2016;Wang et al, 2019), and reduced Reelin levels have been observed in the brains of patients with schizophrenia (Impagnatiello et al, 1998;Guidotti et al, 2000), bipolar disorder (Guidotti et al, 2000), autism (Fatemi et al, 2001;Fatemi et al, 2005), and Alzheimer's disease (Chin et al, 2007). Moreover, heterozygous reeler mice and Reelin ΔC-KI mice exhibit similar neurochemical, behavioral, and cognitive abnormalities to those observed in autism or schizophrenia (Costa et al, 2001;Tremolizzo et al, 2002;Carboni et al, 2004;Nullmeier et al, 2011;Sakai et al, 2016;Sanchez-Hidalgo et al, 2022). The anatomical abnormalities we observed in heterozygous yotari mice may also be related to behavioral defects because layer 1 and hippocampus are essential for higher-order cognitive functions (Hainmueller and Bartos, 2020;Schuman et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, higher plasma levels of reelin were observed in patients with AUD compared with controls. Altered reelin levels in the brain, CSF, or plasma have been reported in animal models and humans with several neuropsychiatric disorders ( Ishii et al, 2016 ; Sánchez-Hidalgo et al, 2022 ). However, most studies are genetic or focused on brain reelin levels, and the exact contribution of peripheral reelin to cognition is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the dysregulation of Reelin protein is associated with various neurological disorders, including schizophrenia, BD, autism, depression, and more [ 39 , 40 ]. Reelin was found to be altered in various animal models of schizophrenia, suggesting its key role in the pathogenesis of schizophrenia [ 41 ]. Reelin levels were significantly reduced in schizophrenia patients, with specific gender differences [ 42 ].…”
Section: Altered 5mc Pattern In Schizophreniamentioning
confidence: 99%